Infantile Aspergillus fumigatus ventriculitis successfully treated with monitoring of plasma and cerebrospinal fluid voriconazole concentration level. Issue 1 (January 2020) - Furudate, Aiko; Hirose, Shoko; Abe, Kota; Kawashima, Akitsugu; Hashimoto, Kazutoshi; Yamazaki, Shingo; Kamei, Katsuhiko; Ishiwada, Naruhiko; Hamada, Hiromichi; Sato, Masahiko
Abstract: Aspergillosis is a rare fungal infection in newborns, and its morbidity and mortality are high. Voriconazole (VRCZ) is the first-line antifungal agent for invasive Aspergillus infection, but little data is available about its pharmacokinetics in infants. We report a case of a premature infant who developed ventriculitis due to Aspergillus fumigatus and received combination antifungal therapy including VRCZ. β-D glucan and Aspergillus antigen index were elevated in the cerebrospinal fluid (CSF). We titrated the dose of VRCZ by monitoring plasma and CSF concentrations. The CSF to plasma concentration ratio of VRCZ ranged from 0.47 to 1.36 (median 0.71). While VRCZ adequately penetrates the blood-brain barrier, its concentration is highly variable in infants.